Akumulasi senyawa sianida, krom, mangan, besi pada air baku dan penilaian risiko kesehatan masyarakat di Kecamatan Babakan Madang Kabupaten Bogor - Basuki Rachmat; Purnama Sidebang; Ikha Purwandari (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Purpose: this study aims to obtain an overview of exposure to cyanide, chromium, manganese and iron exposure to raw water, as well as public health conditions in the Babakan Madang sub-district of Bogor Regency in 2017.Method: A cross-sectional study design, by Public Health Assessment ( PHA). The population in this study were residents of Kadumanggu Village, with a sample of 178 people. Environmental samples in the form of raw water sources, well water as many as 9 points and water times as much as 5 points. Results: In getting the average concentration of cyanide (CN), manganese (Mn), chromium (Cr), and iron (Fe) in well water respectively are 0,002 mg/L; 0.4 mg/L; 0.065 mg/L; and 0.04 mg/L. Based on the results of the analysis of the concentration data, RQ values of cyanide, manganese, chromium and iron were obtained in children, adolescents, and adults with a value of less than one (RQ <1).Conclusion: shows that there are no health effects caused by consuming well water in the area.